Effect Of Compensation And Workload On Employee Retention at Pt. Putra Mahalona East Luwu Regency - Magfirah Indah Ramadani; Indra Kusdarianto; Haedar Haedar (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to analyze the effects of compensation and workload on employee retention at PT. Putra Mahalona in East Luwu Regency, both partially and simultaneously. Methodology: This study employs a quantitative approach using a survey method. The study population consists of 417 employees of PT. Putra Mahalona, with a sample of 208 respondents determined using the Slovin formula and simple random sampling. Data collection was conducted by distributing questionnaires using a Likert scale. The data analysis techniques used included validity and reliability tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²) using SPSS software. Results: The results of the study indicate that compensation has a positive and significant effect on employee retention. Meanwhile, workload does not have a significant partial effect on employee retention. However, when considered simultaneously, compensation and workload have a significant effect on employee retention. The coefficient of determination (R²) value of 0.123 indicates that the variables of compensation and workload account for 12.3% of the variation in employee retention. Findings: The research findings confirm that compensation is a key determinant of retention, while workload alone does not significantly influence retention. Novelty & Originality: The novelty of this study lies in examining the effects of compensation and workload on employee retention in the mining sector in East Luwu Regency, an area that has been relatively under-researched compared to other industrial sectors. Conclusions: The study concludes that compensation plays a more dominant role in employee retention than workload. Type of Paper: This paper is an empirical research paper.